BRINGING SET AND COSTUME DESIGNS TO FRUITION : made by teams. - Dasher, Jennifer ([Place of publication not identified] : FOCAL, 2023)
Bringing Set and Costume Designs to Fruition: Made by Teams dives into the collaborative working relationships between set and costume designers with their technical counterparts throughout the theatrical production process, from concept to execution. Set and costume designers render environments and characters for a wide array of performative events; skilled artisans and technologists bring these visions to life. This book explores the dynamic between those who decide what the set and costumes should look like and those who make them work, including scene designers, costume designers, scene shops, and costume shops. The book discusses how to identify resources, ask the right questions, and engage in healthy collaborations. Following these fundamentals are practical activities and interviews with industry professionals that demonstrate how these skills can be applied to a broad range of productions and other avenues for creative design and production. Bringing Set and Costume Designs to Fruition is written for emerging professionals in set and costume design, as well as students in courses across a theatre degree program, including stagecraft, costume construction, scene design, and introduction to theatrical design and production.
Keywords: Theaters -- Stage-setting and scenery; Costume design; Teams in the workplace; Theater -- Production and direction; PERFORMING ARTS / Theater / Stagecraft